Making Trash Cans as a Form of Environmental Care for Residents of Lok Rawa Village, Mandastana District, Barito Kuala Regency - Muhammad Fitriansyah; Dyah Pradhitya Hardiani; Elia Anggarini (UrbanGreen Central Media, 2022)
One of the problems that occur in Lok Rawa Village is the problem of waste. Every day, local residents produce both organic and non-organic waste, meanwhile, temporary waste collection sites are still limited. As a result, if the waste is not managed properly it will cause the accumulation of garbage and pollution in the environment around the residents. In addition, the awareness of the community about the importance of disposing of waste is still low, it can be seen that a lot of garbage is scattered and the disposal is not in the right place. Making trash bins that have more functions as disposal by giving different colors with the aim of separating organic, inorganic and B3 waste can provide a solution to the waste problem in Lok Rawa Village as well as provide education to the public on the classification of waste generated from households so that will create a comfortable and clean environment.